2022
DOI: 10.1155/2022/3095749
|View full text |Cite
|
Sign up to set email alerts
|

Gallium(III) Complex with Cloxyquin Ligands Induces Ferroptosis in Cancer Cells and Is a Potent Agent against Both Differentiated and Tumorigenic Cancer Stem Rhabdomyosarcoma Cells

Abstract: In this work, gallium(III) complex with cloxyquin (5-chloro-8-quinolinol, HClQ) ligands is shown to effectively inhibit proliferation of rhabdomyosarcoma cells, the frequent, aggressive, and poorly treatable cancer of children. It offers striking selectivity to cancer cells compared to noncancerous human fibroblasts. The data reveal that the complex induces ferroptosis in rhabdomyosarcoma cells, likely due to interfering with iron metabolism. Importantly, it can kill both bulk and stem rhabdomyosarcoma cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Ga(III) competes with iron for transferrin binding which allows it to penetrate “iron-hungry” cancer cells and exhibit its physiological effects—impairment of DNA synthesis, disruption of mitochondrial function, overall inhibition of iron-dependent enzymes, generation of ROS and ultimately, apoptosis [ 83 ]. As the search for novel, metal-based anticancer drugs intensifies, scientific interest into Ga(III) complexes with antiproliferative action has been revitalized over the past decade [ 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. The relatively low number of studies, performed so far, combined with the intrinsic anticancer properties of the Ga(III) ion itself present an exciting possibility for research into novel complexes with biologically active ligands and potential antiproliferative action.…”
Section: Novel Metal Complexes In Cancer Therapymentioning
confidence: 99%
“…Ga(III) competes with iron for transferrin binding which allows it to penetrate “iron-hungry” cancer cells and exhibit its physiological effects—impairment of DNA synthesis, disruption of mitochondrial function, overall inhibition of iron-dependent enzymes, generation of ROS and ultimately, apoptosis [ 83 ]. As the search for novel, metal-based anticancer drugs intensifies, scientific interest into Ga(III) complexes with antiproliferative action has been revitalized over the past decade [ 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. The relatively low number of studies, performed so far, combined with the intrinsic anticancer properties of the Ga(III) ion itself present an exciting possibility for research into novel complexes with biologically active ligands and potential antiproliferative action.…”
Section: Novel Metal Complexes In Cancer Therapymentioning
confidence: 99%
“…Cells were marked with a declined level of GPx4 as well as elevated levels of ROS and lipid peroxides. Ferroptosis was in this case considered the prevalent type of reported cell death, followed by autophagy; the induction of the latter can be associated with the effect caused by free HClQ [ 80 ].…”
Section: Gallium Salts Complexes and Nanoparticlesmentioning
confidence: 99%
“…This suggests that one of the pathways by which RAS drives the occurrence and progression of RMS is to confer ferroptosis resistance to RMS cells. In addition, a recent work found that tris (5-chloro-8-quinolinololato) gallium (III) complex had an active anti proliferation effect on RMS cells, and its efficacy decreased under the co incubation of fer-1 ( Hreusova et al, 2022 ). Meanwhile, cells treated with tris (5-chloro-8-quinolinololato) gallium (III) complex presented typical characteristics of ferroptosis, such as down-regulation of GPX4 expression and accumulation of lipid peroxide ( Hreusova et al, 2022 ).…”
Section: The Role Of Ferroptosis In Skeletal Muscle Diseasesmentioning
confidence: 99%
“…In addition, a recent work found that tris (5-chloro-8-quinolinololato) gallium (III) complex had an active anti proliferation effect on RMS cells, and its efficacy decreased under the co incubation of fer-1 ( Hreusova et al, 2022 ). Meanwhile, cells treated with tris (5-chloro-8-quinolinololato) gallium (III) complex presented typical characteristics of ferroptosis, such as down-regulation of GPX4 expression and accumulation of lipid peroxide ( Hreusova et al, 2022 ). These results suggest that ferroptosis may be a potential mechanism for this compound to exert RMS therapeutic effect.…”
Section: The Role Of Ferroptosis In Skeletal Muscle Diseasesmentioning
confidence: 99%